The World Book encyclopedia of people and places. (World Book, 2000)
It's the illustrations that make kids eyes open wide when they see this lavish set of world-travel books for children. This six-volume set takes students on a worldwide tour of 193 countries. With accurate and up-to-date information, this award-winning set provides students with a clear understanding of today's changing and challenging world. There are full-color maps and charts, flags, time lines, and outstanding copy written from a young person's perspective. Fact boxes for each article provide for quick and easy reference. All of this adds to a new understanding of the history, geography, politics, and economics of our fascinating world of people and places. From China to Chad, New Zealand to Iceland, it's all covered with breathtaking photography you can expect only from World Book. Titles include: Volume 1: Afghanistan-The Czech Republic Volume 2: Denmark-Hungary Volume 3: Iceland-Luxembourg Volume 4: Macedonia-Rwanda Volume 5: St. Kitts/Nevis-Tuvalu Volume 6: Uganda-Zimbabwe/Index Key benefits include:600 full-color illustrations that capture students interest and help meet their educational needs. A concise overview of the history, geography, politics, and economics of our fascinating world. From Afghanistan to Zimbabwe, nations are presented with the clear text and breathtaking photography you have come to expect from World Book. A-Z organization allowing students to locate each country with ease. Nearly 800 full-color maps and 600 charts and graphs. Comprehensive profile of each country providing an overview of its history, geography, economy, people, culture, and government. Helpful time lines that list significant events, with color bars signifying different periods of time for easy reference. Fact box for each country that highlights important data. 87-page cumulative index of 14,000 entries at the end of volume 6. Country Web site listings in volume 6.